Oop vir interpretasie: an examination of the South African media's take-up and representation of the music of Fokofpolisiekar - Kahn, Rebecca (My University, 2010)
ABSTRACT Popular music is rarely seen as a valid vehicle for public debate anywhere in the world, and especially in South Africa. Popular music is traditionally seen as “low art” – to be reported in the arts and entertainment pages of publications, and nothong more. The music of Afrikaans punk band Fokofpolisiekar, however, has been a catalyst for public debate in both the Afrikaans and English print media, in editorial and opinion pages as well as in the news sections of publications. Drawing on theories of the public sphere, public intellectual life and the media, this research shows that the media’s response to the band has brought many discussions around Afrikaner identity in post-apartheid South Africa into the public sphere, beyond the arts and entertainment pages of newspapers, and that through the act of cultural consecration by other public intellectual figures, the band has been validated as commentators in the South African public sphere.